Effect of core and shell compositions on MeOx@LaySr1−yFeO3 core–shell redox catalysts for chemical looping reforming of methane. (1st November 2015) - Neal, Luke; Shafiefarhood, Arya; Li, Fanxing
Highlights: Mn and Co oxides are incorporated into MeO x @LSF core–shell catalysts for CLR. The selectivity of the system is highly dependent on the core composition. The coking of the catalyst is correlated to the properties of the core metal. La stabilizes the perovskite phases, but Sr binds iron into the mixed metal oxides. Abstract: The chemical looping reforming (CLR) process converts methane into syngas through cyclic redox reactions of an active lattice oxygen (O 2 − ) containing redox catalyst. In CLR, methane is partially oxidized to CO and H2 using the active lattice oxygen of a redox catalyst. In a subsequent step, the oxygen-deprived redox catalyst is regenerated by air. Such a process can eliminate the need for steam and/or oxygen in reforming, thereby improving methane conversion efficiency. A number of perovskite-structured mixed metal oxides are known to be active for CLR. However, the oxygen storage capacity of perovskites tends to be low, limiting their practical application in chemical looping. In contrast reducible metal oxides such as cobalt and iron oxides can store up to 30 wt.% lattice oxygen but are less selective for syngas generation. We explore oxygen carriers that utilize the advantages of both perovskites and first-row transition metal oxides by integrating a transition metal oxide core with a mixed ionic–electronic conductive (MIEC) perovskite support/shell. MIEC perovskites facilitate countercurrent conduction of O 2 − and electrons, allowing facile O 2 − transport though the solid. It is proposed that this conduction allows rapid oxygen transport to and from the transition metal oxide cores irrespective of the porosity of the redox catalyst. In this work, we show that MeO x @La y Sr1 − y FeO3 can be an excellent model catalyst system for CLR. The activity, selectivity, and coke resistance of the core–shell system can be tuned by changing the ratio of La to Sr in the perovskite shell and the type of transition metal oxide in the core. Our studies indicate that lower Sr loadings can improve activity and selectivity of the catalyst for methane partial oxidation, but make the LSF shell less resistant to decomposition during the reduction step.